Enhancing energy efficiency in wireless mesh networks through time-synchronized sleep scheduling and low-power hardware - Rifki Muhendra; Dede Rukmayadi; Solihin Solihin (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2026)
Energy efficiency remains a critical challenge in wireless mesh networks (WMNs), particularly for internet of things (IoT) deployments with battery powered nodes and multihop communication. This paper proposes a time synchronized sleep scheduling framework that integrates a lightweight regression-based time synchronization model with low-power hardware to reduce energy consumption in long range (LoRa)-based WMNs. The proposed mechanism aligns local node clocks with a global reference using slope and offset correction, enabling synchronized active and sleep states across nodes. This coordination significantly reduces idle listening and unnecessary radio-on time. The proposed approach is validated through real world experiments on a multihop LoRa mesh testbed with up to three hops. Results show a substantial improvement in energy efficiency, reducing cumulative energy consumption from 125.31 mWh to 28.18 mWh over 10 hours (77.5% reduction). The sleep-mode current is reduced to 0.01 mA, demonstrating effective duty cycling. Furthermore, the approach maintains stable routing, bounded latency, and high packet delivery ratio (PDR). These findings confirm that accurate time synchronization is a key enabler for energy-efficient and reliable multihop communication, providing a practical solution to extend the operational lifetime of IoT-based WMNs.